An experimental and numerical investigation of CO2 corrosion in a rapid expansion pipe geometry. (1st April 2020) - Owen, Joshua; Godfrey, Jack; Ma, Wenlong; de Boer, Greg; Al-Khateeb, Mohammed; Thompson, Harvey; Neville, Anne; Ramsey, Callum; Barker, Richard
Highlights: Investigation of flow-induced corrosion of carbon steel in rapid expansion geometry. Custom designed rapid expansion fittings and flush mounted coupons. Computational fluid dynamics (CFD) predictions of mass transfer coefficients. CFD simulations combined with empirical model to predict CO2 corrosion rates. 4 % difference between experimental and theoretical corrosion rates. Abstract: A combined experimental and numerical methodology for accurately translating Rotating Cylinder Electrode (RCE) CO2 corrosion data to complex pipe flow geometries is presented. Computational Fluid Dynamics (CFD) simulations are used to determine the local variation in mass-transfer coefficient throughout a rapid expansion (as an example geometry). An empirical correlation between mass-transfer coefficient and corrosion rate derived from RCE experiments is then integrated into the CFD model to predict the variation in corrosion rate throughout the fitting. Electrochemical and mass loss corrosion experiments using carbon steel coupons integrated into a 3D printed rapid expansion within a flow loop validate the approach.